Standard Cannulation versus Fistulotomy for Biliary Access in Endoscopic Retrograde Cholangiopancreatography: Should We Expect the Same Success when Treating Choledocholithiasis? - Moreira,Marta (2024)
Abstract Introduction: To access the common bile duct in endoscopic retrograde cholangiopancreatography (ERCP), needle-knife ﬁstulotomy (NKF) can be associated with a shorter sphincterotomy compared to standard cannulation. We aimed to compare the success and safety of NKF versus standard cannulation in the treatment of choledocholithiasis. Methods: A cohort of 379 naïve patients with choledocholithiasis who underwent ERCP between 2005 and 2022 was retrospectively analyzed. The patients were divided into two groups: group A (179 consecutive patients) underwent NKF, while group B (180 patients) received standard biliary access and were matched for stone characteristics and ERCP year. Results: Stone removal success rate for group A was signiﬁcantly lower than that for group B in the initial ERCP (82.0% vs. 92.1%, p = 0.003). In group A, success rates for stone removal were 90.2%, 80%, and 29.4% for stone sizes <10 mm, 10 mm-15 mm, and >15 mm, respectively (p < 0.001). In contrast, group B showed success rates of 99.2%, 81.5%, and 71.4% for the same stone size categories (p < 0.001). Pancreatitis occurred in 3.7% of group A and 5.8% of group B patients (p = 0.340). Regression analysis revealed that NKF cannulation, stone size (>10 mm), and having 4 or more stones were associated with lower stone removal success compared to standard cannulation in the initial ERCP (OR 0.34, p = 0.015; stone size 10-15 mm: OR 0.20, p < 0.001; stone size >15 mm: OR 0.05, p < 0.001; 4 or more stones: OR 0.4, p = 0.040). Conclusions: The removal of common bile duct stones after NKF access, although safe and effective, is less successful than after a standard can-nulation, especially at the baseline ERCP.